2010
DOI: 10.1016/j.bbrc.2010.07.105
|View full text |Cite
|
Sign up to set email alerts
|

Variable loss of Kir4.1 channel function in SeSAME syndrome mutations

Abstract: SeSAME syndrome is a complex disease characterized by seizures, sensorineural deafness, ataxia, mental retardation, and electrolyte imbalance. Mutations in the inwardly rectifying potassium channel Kir4.1 (KCNJ10 gene) have been linked to this condition. Kir4.1 channels are weakly rectifying channels expressed in glia, kidney, cochlea and possibly other tissues. We determined the electrophysiological properties of SeSAME mutant channels after expression in transfected mammalian cells. We found that a majority … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
44
2
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(51 citation statements)
references
References 30 publications
3
44
2
2
Order By: Relevance
“…Tang et al 38 investigated most of the published SeSAME/ EAST mutations in HEK293 cells (G77R and the compound heterozygous mutations were not studied), and they showed decreases in current, qualitatively similar to our results. Although both our group and Reichold et al 37 saw a further decrease in fractional current when Kir5.1 was coexpressed with mutants in a 10:1 ratio, Tang et al 38 saw less of a decrease in current using a 1:1 coexpression ratio.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…Tang et al 38 investigated most of the published SeSAME/ EAST mutations in HEK293 cells (G77R and the compound heterozygous mutations were not studied), and they showed decreases in current, qualitatively similar to our results. Although both our group and Reichold et al 37 saw a further decrease in fractional current when Kir5.1 was coexpressed with mutants in a 10:1 ratio, Tang et al 38 saw less of a decrease in current using a 1:1 coexpression ratio.…”
Section: Discussionsupporting
confidence: 89%
“…Although both our group and Reichold et al 37 saw a further decrease in fractional current when Kir5.1 was coexpressed with mutants in a 10:1 ratio, Tang et al 38 saw less of a decrease in current using a 1:1 coexpression ratio. This group also found that coexpression of the mutants 1:1 with WT led to "rescue" of all currents (including those arising from WT/C140R and WT/ R199X) to WT/WT levels, whereas we found reductions relative to WT/WT of 40% and 55%, respectively, for these two constructs ( Figure 3B).…”
Section: Discussionmentioning
confidence: 45%
See 2 more Smart Citations
“…"EAST" and "SeSAME" syndromes were reported independently by different groups, but consist mostly of identical symptoms: GTCS, ataxia, hearing loss and abnormal excretion of electrolytes ( Table 2). The most frequent mutation of KCNJ10 was R65P at the cytoplasmic end of the first transmembrane region (TM-1) and others include G77R (TM-1), C140R (extracellular loop between TM-1 and TM-2), T164I, A167V (cytoplasmic end of TM-2), R175Q, R199X and R297C (C-terminal domain) [50][51][52] . All these Kir4.1 mutations caused drastic decreases in K + buffering currents conducted not only by Kir4.1 channels, but also by Kir4.1/5.1 channels.…”
Section: Kir41 Channels and Human Epileptic Disordersmentioning
confidence: 99%